2021
DOI: 10.1007/s00039-021-00577-1
|View full text |Cite
|
Sign up to set email alerts
|

A numerical criterion for generalised Monge-Ampère equations on projective manifolds

Abstract: We prove that generalised Monge-Ampère equations (a family of equations which includes the inverse Hessian equations like the J-equation, as well as the Monge-Ampère equation) on projective manifolds have smooth solutions if certain intersection numbers are positive. As corollaries of our work, we improve a result of Chen (albeit in the projective case) on the existence of solutions to the J-equation, and prove a conjecture of Székelyhidi in the projective case on the solvability of certain inverse Hessian equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…In [3,Conjecture 1.4], Collins-Jacob-Yau predicted that the existence of solution to the supercritical dHYM equation is equivalent to a stability condition in terms of holomorphic intersection numbers for any irreducible subvarieties V ⊂ X, modeled on the Nakai-Moishezon criterion, and confirmed it for complex surfaces. In [2], the authors and Takahashi confirmed the conjecture in the projective case building on the works of Chen [1] and Song [12], see also [7,9].…”
Section: Introductionmentioning
confidence: 73%
“…In [3,Conjecture 1.4], Collins-Jacob-Yau predicted that the existence of solution to the supercritical dHYM equation is equivalent to a stability condition in terms of holomorphic intersection numbers for any irreducible subvarieties V ⊂ X, modeled on the Nakai-Moishezon criterion, and confirmed it for complex surfaces. In [2], the authors and Takahashi confirmed the conjecture in the projective case building on the works of Chen [1] and Song [12], see also [7,9].…”
Section: Introductionmentioning
confidence: 73%
“…[11,32,36]. This equation, when solvable (see [6,9,15,38]), gives a unique way, compatible with mirror symmetry and expressing a vanishing moment map condition, to fix the B-field, for each choice of Kähler form ω.…”
Section: Deformed Hermitian Yang-mills Connectionsmentioning
confidence: 99%
“…The uniform version of the conjecture is proved by Gao Chen [Che21] and it is also proved that the uniform conditions are equivalent to the uniform J-stability. The original version of the conjecture is proved by Datar-Pingali [DP21] in a projective case and by Song [Son20] in general. Now we state the converse implication.…”
Section: Introductionmentioning
confidence: 96%